2009
DOI: 10.1124/mol.109.059733
|View full text |Cite
|
Sign up to set email alerts
|

Role of Helix 8 of the Thyrotropin-Releasing Hormone Receptor in Phosphorylation by G Protein-Coupled Receptor Kinase

Abstract: The thyrotropin-releasing hormone (TRH) receptor undergoes rapid and extensive agonist-dependent phosphorylation attributable to G protein-coupled receptor (GPCR) kinases (GRKs), particularly GRK2. Like many GPCRs, the TRH receptor is predicted to form an amphipathic helix, helix 8, between the NPXXY motif at the cytoplasmic end of the seventh transmembrane domain and palmitoylation sites at Cys335 and Cys337. Mutation of all six lysine and arginine residues between the NPXXY and residue 340 to glutamine (6Q r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Helix 8 and B 2 R-GRK Interaction-Whereas the publications so far have focused almost exclusively on a role of helix 8 in receptor expression or in G protein activation, it was just recently reported that helix 8 might also play a role in receptor phosphorylation and, therefore, in the interaction with GRKs (18). Mutation of basic residues in the helix 8 of the thyrotropin releasing hormone receptor resulted in reduced receptor internalization and phosphorylation that could be rescued partly by overexpression of GRK2 or -3 and fully by overexpression of GRK5 or -6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Helix 8 and B 2 R-GRK Interaction-Whereas the publications so far have focused almost exclusively on a role of helix 8 in receptor expression or in G protein activation, it was just recently reported that helix 8 might also play a role in receptor phosphorylation and, therefore, in the interaction with GRKs (18). Mutation of basic residues in the helix 8 of the thyrotropin releasing hormone receptor resulted in reduced receptor internalization and phosphorylation that could be rescued partly by overexpression of GRK2 or -3 and fully by overexpression of GRK5 or -6.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have not only shown the involvement of helix 8 in G protein activation (11-15) but also identified hydrophobic residues in helix 8 as essential for the surface expression of the GPCRs investigated (11,16,17). In addition, it has been published only recently that mutation of positively charged residues in helix 8 of the thyrotropin releasing hormone receptor prevented GRK-mediated receptor phosphorylation (18).As demonstrated by our research group, mutation of Tyr7.53 (Ballesteros/Weinstein nomenclature (19)) to an alanine in the NPXXY sequence resulted in constitutive receptor phosphorylation and internalization (20). Homology modeling indicated that Tyr7.53 in the B 2 R exerts an aromatic stacking interaction with the highly conserved phenylalanine Phe7.60 in helix 8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HEK293 cells were transfected with 900 ng of V5-Ost␣ and 100 ng of each 3ϫHA-Ost␤ species DNA in 24-well plates. At 48 h after transfection, cell surface ELISA was conducted as described previously (17). Briefly, plates were incubated with monoclonal anti-V5 (Invitrogen) and anti-HA (Covance) at 1:5,000 followed by anti-mouse IgG-HRP (BioRad) at 1:5,000.…”
Section: Methodsmentioning
confidence: 99%
“…Surface expression of N-terminally HA-tagged receptors was quantified as described (Gehret et al 2010). Briefly, the N-terminally tagged receptors were transiently expressed in COS-7 cells and 24 hours after transfection the cells were harvested, seeded in 12 well plates and serum-starved overnight.…”
Section: Cell Surface Elisamentioning
confidence: 99%